Sensing and signalling mechanical stress during intercalary growth in Epichloë grass endophytes : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy (PhD) in Genetics at Massey University, Manawatu, New Zealand - Ariyawansa, Kahandawa Geeganaarachchige Sameera (Massey University, 2015)
𝘌𝘱𝘪𝘤𝘩𝘭𝘰𝘦̈ 𝘧𝘦𝘴𝘵𝘶𝘤𝘢𝘦 is an agronomically important seed-transmitted endophytic fungus that grows symbiotically within the intercellular spaces of temperate grass species. This fungus has previously been shown to undergo hyphal intercalary growth during host leaf colonization, a highly unusual mechanism of division and extension in non-apical compartments in vegetative hyphae, as an adaptation to colonise rapidly elongating host cells in the developing leaf. However the exact mechanism that triggers intercalary growth was not known. In this study I aimed to test the hypothesis that intercalary growth is stimulated by mechanical stretch imposed by attachment of hyphae to elongating host cells, and that this stress is sensed by mechano-sensors located on hyphal membranes. To test this hypothesis a novel technique was designed and optimised to stretch fungal hyphae under 𝘪𝘯 𝘷𝘪𝘵𝘳𝘰 conditions. Investigation of un-stretched hyphae showed that de novo compartmentalization occurs in sub-apical compartments of 𝘌. 𝘧𝘦𝘴𝘵𝘶𝘤𝘢𝘦 hyphae according to a compartment length-dependent hierarchy. Subjecting these sub-apical compartments to mechanical stretching showed that hyphal compartment lengths can be increased while maintaining viability, provided that the stretch is within tolerable limits. It further showed that the stretched compartments undergo 𝘥𝘦 𝘯𝘰𝘷𝘰 compartmentalization (nuclear division and septation) similar to un-stretched hyphae but at a significantly higher rate, fulfilling the basic requirements for intercalary growth. 𝘌. 𝘧𝘦𝘴𝘵𝘶𝘤𝘢𝘦 WscA and MidA, which are orthologues of a yeast cell wall stress and a stretch-activated calcium channel protein respectively, were functionally characterized in order to test the possible involvement of these mechano-sensors in intercalary growth. Their roles in general hyphal apical growth, cell wall construction and integrity maintenance during growth in culture were confirmed. The limited ability of Δ𝘮𝘪𝘥𝘈 mutants to colonise developing leaves indicated a possible role in intercalary growth, while Δ𝘸𝘴𝘤𝘈 mutants showed wild-type levels of host colonization. In future, the Δ𝘮𝘪𝘥𝘈 and Δ𝘸𝘴𝘤𝘈 mutants will be subjected to mechanical stretch 𝘪𝘯 𝘷𝘪𝘵𝘳𝘰 to further understand their roles in mechano-sensing and intercalary growth. Given the possible involvement of the stretch-activated calcium channel MidA in intercalary growth, a successful technique was developed to study calcium signalling and distribution in 𝘌. 𝘧𝘦𝘴𝘵𝘶𝘤𝘢𝘦 using the genetically-encoded calcium sensor GCaMP5. Investigations revealed the presence of MidA-driven Ca²⁺ pulses confined to the hyphal tips with unique signatures of temporal and spatial dynamics generated by influx of Ca²⁺. The presence of active sub-apical Ca²⁺ uptake systems were confirmed, manifested as occasional Ca²⁺ pulses in sub-apical compartments that seemed to increase in frequency with mechanical perturbation, indicating a potential crucial role in mechanical stress-driven intercalary growth. In conclusion a prospective model for intercalary growth in the leaf expansion zone is proposed. Mechanical stretching of hyphae results in increased compartment lengths, accompanied by compartmentalization in sub-apical compartments that allows hyphae to extend along their length. Membrane distortion due to stretching activates MidA, triggering a calcium signalling cascade to stimulate cell wall synthesis and other cellular processes.
Keywords: Epichloe; Endophytic fungi; Growth; Genetics